Estrategia didáctica basada en el aprendizaje significativo para la comprensión del concepto de espacio geográfico en estudiantes del grado 7 (2020)
In the present research work, elements that seek to strengthen the processes of understanding social learning are related. This includes elements of spatiality, temporality, culturality and institutionality that help to understand the concept of geographical space. Students from grade 7-4, from the seat of the educational institution Sagrado Corazon: Pedro Antonio Molina, in the municipality of Cerrito-Valle del Cauca, present difficulties in orientation and location in the field when they are faced with a situation of understanding the space where they live, as well as difficulty in relating the concept to categories other than physical and non-identification of the human being as an active part of the geographic space. For this reason, this research work proposes a strategy to generate meaningful learning through an alternative that facilitates the identification, interpretation and analysis of their daily context. The strategy is based on a Participation Action Research approach where the student is the protagonist of the construction of his own knowledge through practical exercises of orientation, spatial location, terrain recognition and the use of cartography. In this way, the research allowed the students to recognize their territory, their culture, their history and the importance of the human being in the development of their environment and the understanding of the concept of geographic space.